Epidemiology of nontuberculous mycobacteria isolations among central North Carolina residents, 2006–2010. Issue 6 (June 2016) - Smith, Genee S.; Ghio, Andrew J.; Stout, Jason E.; Messier, Kyle P.; Hudgens, Edward E.; Murphy, Mark S.; Pfaller, Stacy L.; Maillard, Jean-Marie; Hilborn, Elizabeth D.
Summary: Background: Nontuberculous mycobacteria (NTM) are environmental mycobacteria associated with a range of infections. Reports of NTM epidemiology have primarily focused on pulmonary infections and isolations, however extrapulmonary infections of the skin, soft tissues and sterile sites are less frequently described. Methods: We comprehensively reviewed laboratory reports of NTM isolation from North Carolina residents of three counties during 2006–2010. We describe age, gender, and race of patients, and anatomic site of isolation for NTM species. Results: Among 1033 patients, overall NTM isolation prevalence was 15.9/100, 000 persons (13.7/100, 000 excluding Mycobacterium gordonae ). Prevalence was similar between genders and increased significantly with age. Extrapulmonary isolations among middle-aged black males and pulmonary isolations among elderly white females were most frequently detected. Most isolations from pulmonary sites and blood cultures were Mycobacterium avium complex; rapidly growing NTM (e.g. Mycobacterium chelonae, Mycobacterium fortuitum ) were most often isolated from paranasal sinuses, wounds and skin. Conclusions: We provide the first characterization of NTM isolation prevalence in the Southeastern United States (U.S.). Variation in isolation prevalence among counties and races likely represent differences in detection, demographics and risk factors. Further characterization of NTM epidemiology is increasingly important as percentages of immunocompromised individuals and the elderly increase in the U.S. population. Highlights: This is the first summary of NTM clinical isolations in the Southeastern U.S. The highest prevalence of pulmonary NTM isolations occurred among white females. Black males experienced the highest prevalence of extrapulmonary NTM isolations. Isolation of Mycobacterium avium complex predominated among pulmonary sites.